2000
DOI: 10.1177/00220345000790111201
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Dental Decay in Children after Maternal Consumption of Xylitol Chewing Gum, a Follow-up from 0 to 5 Years of Age

Abstract: Studies have shown that prevention of mutans streptococci (MS) colonization in early childhood can lead to prevention of dental decay. In the microbiological part of the present study in Ylivieska, Finland, with 195 mothers with high salivary MS levels, regular maternal use of xylitol chewing gum resulted in a statistically significant reduction in MS colonization in their children's teeth at the age of 2 years compared with teeth in children whose mothers received fluoride or chlorhexidine varnish treatment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
0
29

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(136 citation statements)
references
References 17 publications
7
100
0
29
Order By: Relevance
“…Notably, the now-extensive literature on xylitol inhibition of caries (Mäkinen et al, 1995;Isokangas et al, 2000), usually monitored by measure of frank cavitation of lesions into the dentin, is associated with what might seem to be paradoxical emergence among frequent users of xylitol of X r S. mutans in the mouth (Trahan and Mouton, 1987). The present observations suggest that, in fact, X r strains of S. mutans are of diminished virulence by virtue of compromised colonization of the teeth and compromised ability to induce lesions that penetrate dentin, i.e., to the point that they would have been scored in those clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the now-extensive literature on xylitol inhibition of caries (Mäkinen et al, 1995;Isokangas et al, 2000), usually monitored by measure of frank cavitation of lesions into the dentin, is associated with what might seem to be paradoxical emergence among frequent users of xylitol of X r S. mutans in the mouth (Trahan and Mouton, 1987). The present observations suggest that, in fact, X r strains of S. mutans are of diminished virulence by virtue of compromised colonization of the teeth and compromised ability to induce lesions that penetrate dentin, i.e., to the point that they would have been scored in those clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Xylitol inhibition of caries has attracted considerable interest (Scheinin and Mäkinen, 1975;Mäkinen et al, 1995;Isokangas et al, 2000;Söderling et al, 2000), as has the puzzling emergence, in the mouths of habitual xylitol users, of S. mutans that are resistant to metabolic inhibition by xylitol (X r ) (Trahan and Mouton, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up studies have looked at the occurrence of dental decay in children as well as their plaque and salivary colonisation with mutans streptococci at three and six years of age. 3,4 There was a 74% reduction in dmft seen in the 5-year-olds whose mothers had used the xylitol around the period described as 'the discrete window of infectivity' 40 compared with children whose mothers had used chlorhexidine. There was a 71% reduction in dmft seen in the 5-year-olds whose mothers had used the xylitol compared with children whose mothers had used fluoride varnish.…”
Section: Evidence From Clinical Trialsmentioning
confidence: 99%
“…More recently, remarkable results have emerged from a trial where development of dental caries was much lower in children whose mothers had chewed xylitol gum when their children were young (beginning at three months of age) during the so-called 'discrete window of infectivity' from mother to child (between 19 -31 months of age), compared with control children. 2,3,4 For many years, many thousands of Finnish children have participated in caries preventive programmes which involved chewing xylitol gum in school. 5,6 Disposal of spent gum has been seen as a draw-back for such community programmes by public health authorities in many countries and it was of considerable interest that, in a recently published trial, the caries preventive effectiveness of chewing xylitol sweets was observed to be similar to that of xylitol chewing gum.…”
mentioning
confidence: 99%
“…Several reports have described that the earlier the colonization occurs in a child, the greater the degree of decay in later years (Köhler et al 1988;Straetemans et al 1998;Isokangas et al 2000). Intervention to safeguard the oral health of pregnant women and new mothers with infants can produce benefits for both the mother and child.…”
Section: Introductionmentioning
confidence: 99%